VD_FINDINFO HC / 2021 / 393 vom 10. Oktober 2019 - VD Tribunal cantonal (2019)
VENTE, NULLITÉ PARTIELLE, PRIX D'ACHAT, DEMANDE PARTIELLE | 19 CO, 20 CO, 152 al. 1 CPC (CH), 308 al. 1 let. a CPC (CH), 86 CPC (CH)